The future of environmental ethics - Rolston, Holmes, 1932-2025, author; Cambridge University Press, publisher (Colorado State University. Libraries, 2011)
The environment is on the world agenda, also on the ethical frontier, for the foreseeable future. Environmental ethics is, at times, about saving things past, still present. Environmental ethics is equally about future nature, without analogy in our past. Living at one of the ruptures of history, modern cultures threaten the stability, beauty, and integrity of Earth, and thereby of the cultures superposed on Earth. Environmental ethics must find a satisfactory fit for humans in the larger communities of life on Earth.
Lecture delivered at The Royal Institute of Philosophy, Session 2009 2010, Programme of Public Lectures, The Environment, October 16, 2009.
Keywords: climate change; Earth ethics; biodiversity; respect for life; environmental ethics; end of nature; wilderness; wild nature; global warming